Emergence of FGFR family gene fusions as therapeutic targets in a wide spectrum of solid tumours. Issue 1 (January 2014) - Parker, Brittany C; Engels, Manon; Annala, Matti; Zhang, Wei
Abstract The emergence of fibroblast growth factor receptor (FGFR) family fusions across diverse cancers has brought attention to FGFR‐derived cancer therapies. The discovery of the first recurrent FGFR fusion in glioblastoma was followed by discoveries of FGFR fusions in bladder, lung, breast, thyroid, oral, and prostate cancers. Drug targeting of FGFR fusions has shown promising results and should soon be translating into clinical trials. FGFR fusions form as a result of various mechanisms – predominantly deletion for FGFR1, translocation for FGFR2, and tandem duplication for FGFR3. The ability to exploit the unique targetability of FGFR fusions proves that FGFR‐derived therapies could have a promising future in cancer therapeutics. Drug targeting of fusion genes has proven to be an extremely effective therapeutic approach for cancers such as the recurrent BCR–ABL1 fusion in chronic myeloid leukaemia. The recent discovery of recurrent FGFR family fusions in several cancer types has brought to attention the unique therapeutic potential for FGFR‐positive patients. Understanding the diverse mechanisms of FGFR fusion formation and their oncogenic potential will shed light on the impact of FGFR‐derived therapy in the future. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.